Pengaruh Kreativitas, Inovasi, dan Prilaku Wirausahawan terhadap Kesuksesan Usaha UMKM Kecamatan Kedaton Bandar Lampung - Fisca Adelia Febyani; Luke Suciyati Amna; Nuris Sanida (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of creativity, innovation, and entrepreneurial behavior on the success of culinary MSME businesses in Kedaton District, Bandar Lampung City. The background of this research is based on the important role of MSMEs in the local economy, amid the challenges faced in the competitive food industry. The methodology used is a quantitative approach with data collection through a closed survey to 37 respondents of MSME owners who operate for more than one year and have branches. Data analysis was conducted using SPSS software, with multiple linear regression results showing has a positive and significant influence on business success. Innovation is the most dominant factor in increasing business success, with an R² value indicates that 58.5% of business success is influenced by these three variables. The conclusion of this study confirms the importance of increasing creativity, innovation, and entrepreneurial behavior to achieve success in the culinary business.